Design, user experience, and usability : 6th International Conference, DUXU 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings /: 6th International Conference, DUXU 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings. (2017) - Unknown
No abstract available